Funções exponenciais reais, exponenciais complexas e de matrizes - Lopes, Matusalém Saraiva (2022)
In this work we take a walk through exponential functions. We analyze your concepts basic education, in addition to its application and modeling in High School. Applying Calculus Concepts differential and integral to delve into topics rarely addressed by the teacher of the middle school. All this being considered for the real exponential functions, exponentials for the field of complexes and exponentials for matrices.